2015
DOI: 10.1007/s10048-015-0460-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical heterogeneity associated with KCNA1 mutations include cataplexy and nonataxic presentations

Abstract: Mutations in the KCNA1 gene are known to cause episodic ataxia/myokymia syndrome type 1 (EA1). Here, we describe two families with unique presentations who were enrolled in an IRB-approved study, extensively phenotyped, and whole exome sequencing (WES) performed. Family 1 had a diagnosis of isolated cataplexy triggered by sudden physical exertion in multiple affected individuals with heterogeneous neurological findings. All enrolled affected members carried a KCNA1 c.941T>C (p.I314T) mutation. Family 2 had an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
(19 reference statements)
0
30
0
Order By: Relevance
“…Some affected individuals may also display delayed motor development, choreoathetosis, carpal spasm, cognitive dysfunctions, expressive language delay, and inability to learn a motor task. A short‐sleep phenotype and cataplexy have also recently been reported …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some affected individuals may also display delayed motor development, choreoathetosis, carpal spasm, cognitive dysfunctions, expressive language delay, and inability to learn a motor task. A short‐sleep phenotype and cataplexy have also recently been reported …”
Section: Discussionmentioning
confidence: 82%
“…EA1 may have a broad spectrum of symptoms like ataxia and myokymia. During attacks, additional symptoms may be reported, including vertigo, blurred vision, diplopia, nausea, headache, diaphoresis, body stiffening, and difficulty breathing …”
Section: Discussionmentioning
confidence: 99%
“…The latter is also observed in our study. The phenotype of EA1 patients is highly heterogeneous and may include myokymia, cataplexy, epilepsy, neuromyotonia, paroxysmal dyspnea, and also skeletal defects [13, 15-20]. Of note, episodic ataxia is not present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that KCNA1 and HOXA11 levels were downregulated in disused muscle. HOXA11 negatively regulates the myogenic differentiation expression of the transcription factor myoblast determination protein in muscle precursors (Yamamoto et al 2003), and KCNA1, a gene responsible for myokymia (Brownstein et al 2016), suppresses myogenic contraction. These results suggest a myogenic shift of gene expression in satellite cells derived from disused muscle compared with the intact muscle.…”
Section: Discussionmentioning
confidence: 99%